The mediation role of peer-to-peer lending: the impact of inclusion and self-efficacy on MSMEs financial performance - Safrianti, Sintia; Lakoni, Idham; Yulianasari, Nina; Angel, Frenita Claudia; Perdiansyah, Perdiansyah; Ismiyanti, Fitri (Manajemen dan Bisnis, 2026)
This study aims to examine the role of peer to peer lending (P2P) in mediating the influence of financial self-efficacy, financial literacy, and financial inclusion on the financial performance of MSMEs in Bengkulu City. A study design that was quantitative and explanatory was applied using a survey method involving 108 MSMEs selected through probability sampling across nine districts. Data were collected using questionnaires and analyzed using PLS-SEM with SmartPLS 4.1. The results indicate that financial inclusion and financial self efficacy have a major impact on the adoption of peer to peer lending, while financial literacy does not. Furthermore, peer to peer lending significantly improves financial performance and mediates the effect of financial self efficacy and financial inclusion on performance. Although financial self efficacy, financial literacy, and financial inclusion do not statistically significantly correlate with financial performance. This study is original in integrating behavioral finance constructs with digital peer to peer lending adoption using the Theory of Planned Behavior, contributing empirical evidence to the growing literature on MSME financial performance in underdeveloped regions.